Does Entrepreneurial Career Choice Lessen the Graduate Unemployment Problem? The Case of Malaysian Graduates (Global Business Management Review (GBMR), 2021)
Entrepreneurship has been long regarded as able to lessen the problem of graduate unemployment. This ability of entrepreneurship has been frequently quoted by numerous studies as a motivation of study to engage into the studies of graduate entrepreneurial career choice. Nevertheless, the relationship between the entrepreneurial career choice and graduate unemployment is yet to be explored. This paper aims to estimate the impact of entrepreneurial career choice on the Malaysian graduate unemployment. The targeted population of the present paper was the Universiti Utara Malaysia (UUM) and Universiti Malaysia Kelantan (UMK) graduates. A sample of 1,723 graduates was collected using self-administered questionnaires. The descriptive statistics, cross-tabulation tables and econometrics analysis are employed. Graduate entrepreneurial career choice is found to be unrelated to the chance of being unemployed and unable to reduce the probability of being unemployed among the low employability graduates. Thus, graduate entrepreneurial career choice does not lessen the graduate unemployment problem. However, there is some evidence that entrepreneurial career choice could reduce the unemployment duration and hinder the occurrence of long-term unemployed among the low employability graduates. The Malaysian government policy to combat the graduate unemployment problem could not rely mainly on the entrepreneurial career choice. The graduate entrepreneurial career choice, however, could be relied on reducing the occurrence of long-term unemployment. Future studies are suggested to use the sample of all graduates to validate the findings.